Anatomy and variations in the origin of the vertebral artery - Zhivadinovik Julija; Papazova, Marija; Matveeva, Niki; Dodevski, Ace; Zafirova, Biljana (Macedonian Association of Anatomists and Morphologists, 2011)
The vertebral artery (a. vertebralis, VA) is classically described as the first branch of the ipsilateral subclavian artery (a. subclavia), but multiple variations in the origin of that vessel have been reported in the literature. This examination was made on 110 unselected human hearts without pathoanatomical changes, obtained after autopsy of newborns, fixed in 10% formaldehyde. Standard anatomical methods, inspection and dissection were used for the analyzing of the origin of a. vertebralis. The analysis showed that 102 of the specimens (92.7%) had the usual pattern of the aortic arch and its branches, with the usual topographic relations. In three of the specimens (2.7%) a. vertebralis sinistra had a separate origin between a. carotis communis sinistra and a.subclavia sinistra. In one specimen a. vertebralis sinistra had a separate origin as the fourth branch between a. carotis communis sinistra and a. subclavia sinistra and there was a fifth branch originating distal to a. subclavia sinistra.
Keywords: vertebral artery; anatomy; embryology; variations